Lamin A, Chromatin and FPLD2: Not Just a Peripheral Ménage-à-Trois - Briand, Nolwenn; Cahyani, Inswasti; Madsen-Østerbye, Julia; Paulsen, Jonas; Rønningen, Torunn; Sørensen, Anita L.; Collas, Philippe (Frontiers in Cell and Developmental Biology, 2018)
At the nuclear periphery, the genome is anchored to A- and B-type nuclear lamins in the form of heterochromatic lamina-associated domains. A-type lamins also associate with chromatin in the nuclear interior, away from the peripheral nuclear lamina. This nucleoplasmic lamin A environment tends to be euchromatic, suggesting distinct roles of lamin A on the regulation of gene expression in peripheral and more internal regions of the nucleus. The hot-spot lamin A R482W mutation linked to familial partial lipodystrophy of Dunnigan-type (FPLD2), affects lamin A association with chromatin at the nuclear periphery and in the nuclear interior, and causes 3-dimensional (3D) rearrangements of chromatin. In this mini-review, we highlight features of nuclear lamin association with the genome at the nuclear periphery and in the nuclear interior. We address recent data showing a rewiring of such interactions in FPLD2 patient cells, and in adipose progenitor and induced pluripotent stem cell models of FPLD2. We discuss associated epigenetic and genome conformation changes elicited by the lamin A R482W mutation at the gene level. The findings argue that the mutation adversely impacts global and local genome architecture throughout the nucleus space. The results, together with emerging new computational tools, mark the start of a new era in our understanding of the 3D genomics of laminopathies.